Successful Management of Coronavirus Disease 2019-Related Respiratory Failure Using High-Flow Nasal Cannula Therapy in a Patient with Underlying Pulmonary Artery Hypertension - Kotani, Mariko; Kohyama, Tomoki; Moriyama, Kiyoshi; Yorozu, Tomoko (Case Reports in Pulmonology, 2022)
A case involving a 50-year-old woman (height, 155 cm; weight, 79.6 kg), who was undergoing home oxygen therapy (3.5 L/min), with an oxygen saturation (SpO2) of approximately 91% due to pulmonary artery hypertension (PAH) with mixed connective tissue disease, is reported. The patient developed coronavirus disease 2019- (COVID-19-) related respiratory failure, with an SpO2 of 78% on oxygen inhalation (3.5 L/min) and was admitted to the authors’ hospital. In accordance with remdesivir, dexamethasone, and heparin treatment, high-flow nasal cannula (HFNC) therapy was selected to avoid intubation. At an initial HFNC setting of 70% oxygen with a flow rate of 50 L/min, SpO2 improved to 92% and her subjective symptoms improved. She was weaned from HFNC on day 5 of admission (day 14 of COVID-19 onset) and discharged home on day 14 of admission. In patients with PAH, the beneficial effects of HFNC to avoid endotracheal intubation were evident in avoiding hemodynamic instability and worsening respiratory failure.